Frequency of mortality in patients with high AIMS65 score presenting with upper GI bleed - Khan, Javeria Zahid; Ambreen, Saima; Jahangir, Sidra; Malik, Aimen; Khaar, Bushra; Umar, Muhammad (Journal of Rawalpindi Medical College, 2023)
Introduction: Upper gastrointestinal bleeding is a common reason for hospitalisation across the world, with a UK frequency of 10% and a death rate of 8-14 percent. [1] Several risk assessment scores have been created to predict clinically relevant outcomes like death, the requirement for hospital-based care, rebleeding, and hospital stay length Objective: To determine frequency of mortality in patients with high AIMS65 score presenting with upper gastrointestinal bleeding. Setting: Gastroenterology Department –removed for blind review--- Material & Methods: It was a cross-sectional, prospective, observational research study. Patients having a high AIMS score were recruited in the study. The patient's medical history, physical examination, and biochemical data were all properly recorded. Patients were observed for the outcome variable, which was hospital mortality. Results: 119 patients fulfilling the inclusion criteria were included. There were 77 (64.7%) males and 42 (35.3%) females. The mean age was 43.10 ± 14.213 years On analysis of demographic data, it was observed that 61 (51.3%) patients were below 40 years of age. On analysis of organ dysfunction 79 (66.4%) had cardiovascular dysfunction, 55 (46.2%) had respiratory dysfunction, 39 (32.8%) had renal dysfunction. On outcome variable, It was observed that 81 (68.1%) of the people had died. Conclusion: Majority of the patients with high AIMS had mortality. Majority of the patients were males and had cardiovascular dysfunction. Key words: GERD, endoscopy, gastroduedonal disease, carcinoma, gastritis.